2018
DOI: 10.1371/journal.pone.0192872
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the bioherbicide potential of Eucalyptus globulus Labill: Biochemistry and effects of its aqueous extract

Abstract: In the worldwide search for new strategies in sustainable weed management, the use of plant species able to produce and release phytotoxic compounds into the environment could be an effective alternative to synthetic herbicides. Eucalyptus globulus Labill. is known to be a source of biologically active compounds responsible for its phytotoxic and allelopathic properties. Our previous results demonstrated the bioherbicide potential of eucalyptus leaves incorporated into the soil as a green manure, probably thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 42 publications
2
77
0
10
Order By: Relevance
“…Weeds reduce crop yield by competing for nutrients, light, and moisture [1]. Sustainable weed management is one of the main challenges for both conventional and organic horticulture [2]. Current weed control in horticultural production includes synthetic herbicides and physical methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Weeds reduce crop yield by competing for nutrients, light, and moisture [1]. Sustainable weed management is one of the main challenges for both conventional and organic horticulture [2]. Current weed control in horticultural production includes synthetic herbicides and physical methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical compounds extracted from many plant species have shown allelopathic properties, which give a great hope in the development of non-synthetic alternatives for weed control. Most studies have found allelochemicals mainly in aqueous extracts (Chon et al 2003;Tsao et al 2002;Xuan et al 2005;Hill et al 2007;Reigosa and Pazos-Malvido 2007;Shrestha 2009;Lin et al 2010;Zhang et al 2010;Rueda-Ayala et al 2015;Amari et al 2014;Puig et al 2018), describing almost exclusively inhibitory effects towards germination and root elongation. The aqueous extracts of C. haematocephala used in this study evidenced a high content of chemical compounds that inhibited the development of target species more than ethanol based extracts.…”
Section: Allelopathic Effects On Target Speciesmentioning
confidence: 99%
“…4) than aqueous extracts. Aqueous extracts have shown a joint action of several contained compounds at once (Puig et al 2018).…”
Section: Allelopathic Effects On Target Speciesmentioning
confidence: 99%
See 2 more Smart Citations